Seismic fragility of a highway bridge in Quebec retrofitted with natural rubber isolators - G. H. Siqueira (Revista IBRACON de Estruturas e Materiais)
This paper presents fragility curves for the evaluation of a highway bridge retrofitted with seismic isolator devices. The object of this study is the Chemin des Dalles bridge over Highway 55 located in Trois-Rivières in Quebec, Canada. A series of synthetic ground motions time histories compatible with eastern Canada are used to capture the uncertainties related to the hazard. The seismic isolator model represents natural rubber bearing placed under the longitudinal girders over the bents and the abutments of the bridge. NRB isolators are placed in these locations to uncouple the movement of the superstructure and the infrastructure, increasing the flexibility of the system and decreasing the forces transmitted to the infrastructure. Finally, a set of fragility curves for the as-built and retrofitted models are compared to evaluate the effectiveness of seismic isolation to decrease the seismic vulnerability of this bridge.